Comparison of the Impact of Mentalization-Based Therapy and Unified Transdiagnostic Treatment on Intimacy and Marital Satisfaction of Women with Experience of Marital Infidelity - Larki, Tayebeh; Yousefi, Emad; Khajehpour, Leila (International Journal of Education and Cognitive Sciences, 2022)
Purpose: This study aims to compare the effectiveness of Mentalization-Based Therapy and Unified Transdiagnostic Treatment on marital intimacy and satisfaction among women who have experienced marital infidelity. Methods and Materials: This quasi-experimental study utilized a pre-test and post-test design with a control group. Forty-five women who had experienced marital infidelity were selected through purposive sampling and randomly assigned to three groups: Mentalization-Based Therapy (15 participants), Unified Transdiagnostic Treatment (15 participants), and a control group (15 participants). Data were collected using the Marital Intimacy Questionnaire and the Kansas Marital Satisfaction Scale. Analyses were conducted using Multivariate Analysis of Covariance (MANCOVA) and Analysis of Covariance (ANCOVA), along with the Bonferroni post hoc test. Findings: Both therapeutic approaches significantly increased marital intimacy and satisfaction compared to the control group (p < .05). There was no significant difference in the effectiveness of the two therapies (p > .05), suggesting that both methods are equally effective in improving marital outcomes. Conclusion: Mentalization-Based Therapy and Unified Transdiagnostic Treatment are effective interventions for enhancing marital intimacy and satisfaction in women who have experienced marital infidelity. Both therapies comprehensively address emotional and cognitive disruptions, contributing to improved psychological security and relationship quality.